2014
DOI: 10.1007/s11356-014-2799-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between PAH bioavailability, degrading bacteria, and soil characteristics during PAH biodegradation in five diffusely contaminated dissimilar soils

Abstract: The natural biodegradation of seven polycyclic aromatic hydrocarbons (PAHs) by native microorganisms was studied in five soils from Normandy (France) from diffusely polluted areas, which can also pose a problem in terms of surfaces and amounts of contaminated soils. Bioavailability tests using cyclodextrin-based extractions were performed. The natural degradation of low molecular weight (LMW) PAHs was not strongly correlated to their bioavailability due to their sorption to geosorbents. Conversely, the very lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 47 publications
2
31
1
Order By: Relevance
“…Most of the microbial parameters were also associated with PC-1; thus, it appears that the microbial community in the revegetated coal mine spoil is more effective in degradation of LMW PAHs (Table III). In a similar study, Crampon et al (2014) employed PCA and found the same differential degradation pattern of LMW and HMW PAHs.…”
Section: Correlation and Principal Component Analysismentioning
confidence: 82%
“…Most of the microbial parameters were also associated with PC-1; thus, it appears that the microbial community in the revegetated coal mine spoil is more effective in degradation of LMW PAHs (Table III). In a similar study, Crampon et al (2014) employed PCA and found the same differential degradation pattern of LMW and HMW PAHs.…”
Section: Correlation and Principal Component Analysismentioning
confidence: 82%
“…The detection and quantification thresholds, calculated respectively as 3 and 10 times the standard deviation of the blank sample noise, were 1.5/5 µg L −1 for PHE, 2.5/8.5 µg L −1 for FLT, PYR, BbF and BkF, 3.5/11.5 µg L −1 for BaP and 5/16.5 µg L −1 for BghiP. Again, the complete procedure can be found in Crampon et al (2014) [43]. In this study, we decided to compare only the biodegradation of LMW PAH to the biodegradation of HMW PAH in the five soils.…”
Section: Dissipation Time-course Studiesmentioning
confidence: 91%
“…Pv and SER soils are Gleysols located close to the Seine river (periodically flooded). The soil named TB is a forest soil (Gleysol), also located close to the Seine River, and also periodically flooded [43].…”
Section: Sampling Sitesmentioning
confidence: 99%
See 2 more Smart Citations